Lesser than diabetes hyperglycemia in pregnancy is related to perinatal mortality: a cohort study in Brazil - Wendland Eliana M; Duncan Bruce B; Mengue Sotero S; Schmidt Maria I (BMC, 2011)
Abstract Background Gestational diabetes related morbidity increases along the continuum of the glycemic spectrum. Perinatal mortality, as a complication of gestational diabetes, has been little investigated. In early studies, an association was found, but in more recent ones it has not been confirmed. The Brazilian Study of Gestational Diabetes, a cohort of untreated pregnant women enrolled in the early 1990's, offers a unique opportunity to investigate this question. Thus, our objective is to evaluate whether perinatal mortality increases in a continuum across the maternal glycemic spectrum. Methods We prospectively enrolled and followed 4401 pregnant women attending general prenatal care clinics in six Brazilian state capitals, without history of diabetes outside of pregnancy, through to birth, and their offspring through the early neonatal period. Women answered a structured questionnaire and underwent a standardized 2-hour 75-g oral glucose tolerance test (OGTT). Obstetric care was maintained according to local protocols. We obtained antenatal, delivery and neonatal data from hospital records. Odds ratios (OR) were estimated using logistic regression. Results We ascertained 97 perinatal deaths (67 fetal and 31 early neonatal). Odds of dying increased according to glucose levels, statistically significantly so only for women delivering at gestational age ≥34 weeks (p < 0.05 for glycemia-gestational age interaction). ORs for a 1 standard deviation difference in glucose, when analyzed continuously, were for fasting 1.47 (95% CI 1.12, 1.92); 1-h 1.55 (95% CI 1.15, 2.07); and 2-h 1.53 (95% CI 1.15, 2.02). The adjusted OR for IADPSG criteria gestational diabetes was 2.21 (95% CI 1.15, 4.27); and for WHO criteria gestational diabetes, 3.10 (95% CI 1.39, 6.88). Conclusions In settings of limited detection and treatment of gestational diabetes mellitus, women across a spectrum of lesser than diabetes hyperglycemia, experienced a continuous rise in perinatal death with increasing levels of glycemia after 34 weeks of pregnancy. Current GDM diagnostic criteria identified this increased risk of mortality.